3w+4x-11y+7w+11x+4y=

Simple and best practice solution for 3w+4x-11y+7w+11x+4y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3w+4x-11y+7w+11x+4y= equation:


Simplifying
3w + 4x + -11y + 7w + 11x + 4y = 0

Reorder the terms:
3w + 7w + 4x + 11x + -11y + 4y = 0

Combine like terms: 3w + 7w = 10w
10w + 4x + 11x + -11y + 4y = 0

Combine like terms: 4x + 11x = 15x
10w + 15x + -11y + 4y = 0

Combine like terms: -11y + 4y = -7y
10w + 15x + -7y = 0

Solving
10w + 15x + -7y = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-15x' to each side of the equation.
10w + 15x + -15x + -7y = 0 + -15x

Combine like terms: 15x + -15x = 0
10w + 0 + -7y = 0 + -15x
10w + -7y = 0 + -15x
Remove the zero:
10w + -7y = -15x

Add '7y' to each side of the equation.
10w + -7y + 7y = -15x + 7y

Combine like terms: -7y + 7y = 0
10w + 0 = -15x + 7y
10w = -15x + 7y

Divide each side by '10'.
w = -1.5x + 0.7y

Simplifying
w = -1.5x + 0.7y

See similar equations:

| 14-c/-18=-24 | | 8(2-2x)+16=9 | | -1.45=ln(3t+2) | | 2x+60=5x-60 | | z=3x+4y^2 | | (-20)-(-4m)=(-5m)-(-15) | | -9=-77+x | | U(3U+4)= | | 2x+60+5x-60=180 | | -20-(-4m)=(-5m)-(-15) | | -8b=2 | | 6x=13x-6 | | (6+w)(5w-1)=0 | | 87=94-n | | -14=-1-2v | | -5=x-1+1 | | 4-m=14 | | 1/s^.75=1/2 | | -4=3m+n | | 8x^2-80x+168=0 | | 6=4.50 | | 5x^2-17x-40=(5x+8) | | 8=-4n-4n | | 5v-v=-4 | | -11.6w=-10.8w+15.36 | | 42+y-2y(7)=0 | | d+-729=130 | | 4m+7=-13 | | -8=4p-8p | | 7+3y=-21 | | 8x-6w+3x+7y+2y+2w= | | 3p+4(p-2)=44.50 |

Equations solver categories